Psychosocial and intra-labor risk factors and their relationship with skeletal muscle pain in university professors - Gutierrez-Calderón, Maria Alexandra; Diaz-Therán, Kelly Mercedes (Universidad y Salud, 2021)
Introduction: One of the first conditions for the appearance of skeletal muscle diseases is osteomuscular pain, which is the most frequent factor that increases the risk for occupational illnesses. Objective: To identify the presence of intra-labor psychological factors and their relationship with musculoskeletal pain in professors. Materials and methods: A quantitative descriptive approach with a transactional design was applied with 83 university professors from the city of Sincelejo (Colombia). The Nordic Kourinka questionnaire and the Battery to measure psychosocial risk proposed by the Health and Social Protection Ministry were used. Information was processed with the SPSS 25 software, and data analysis was carried out through trend measures and association tests. Results: Symptoms of pain associated with musculoskeletal diseases were found, with prevalence of neck, dorsal or lumbar column pain. Also, there was a statistically significant difference between the pain variable and psychosocial intra-labor risk, in its work control domain (p>0.05). Conclusion: The timely report of reliable data is important for the assessment and control of pain symptoms and their relationship with labor load internal factors.